Dedicated to the memory of V.A. Briskman - Myznikova, B.I.; Kostarev, K.G. (Perm Federal Research Centre Journal, 2024)
Vladimir Abramovich Briskman (1937–2001), PhD in Physics and Mathematics, the author of many scientific papers and monographs, was the Head of the Laboratory of Hydrodynamic Stability (from 1970 to 2001) at the Institute of Continuous Media Mechanics of the Ural Branch of the Russian Academy of Sciences. He was the Member of the Russian National Committee for Theoretical and Applied Mechanics, the Member of the Space Council of RAS and the Council for New Materials of the Russian Space Agency, the Fellow of the European Society of Mechanics (EuroMech), the European Space Explorers Association (ELGRA), and the Member of Committee on New Materials of the International Academy of Astronautics.